Legal status, powers and functions of the Ministry of Justice of Ukraine in the system of protection of social rights of humans and citizen - Krasnohor, Oleksandr; Krychun, Yurii; Shkliar, Sergii; Provotorov, Oleksandr; Nazarenko, Olha (Interacción y Perspectiva, 2025)
The article examines the institutional role of the Ministry of Justice of Ukraine in the system of protecting the social rights of individuals and citizens. The aim of the article is to determine the legal status, powers and functions of the Minis- try in the context of current political and security challenges, as well as to analyze the key signs of its institutional capacity. For this purpose, a complex of methods is used: analysis and synthesis, logical and semantic, formal and legal, scientific generalization, scientific legalization, causal-inheritance and statistical. The results of the investigation showed that the Ministry of Justice plays a multifunctional role as the central body of the crown government, responsible for the formation of government policy in the field of human and civil rights, coordination free legal assistance, state registries, a preventive mechanism against attacks and the implementation of international standards. A comparative analysis was conducted with the approaches of the EU and the Council of Europe, revealing common features and differences in the institutional protection of social human and civil rights. The emphasis is on strengthening interdepartmental coordination, resource capacity and digitalization of procedures, which will contribute to strengthening the rule of law. The conclusions substantiate the need for further improvement of the regulatory framework, transparency and accountability of the Ministry, as well as more active involvement of civil society to ensure real protection of social rights and freedoms of citizens.